Minimum transmissivity and optimal well spacing and flow rate for high-temperature aquifer thermal energy storage. (1st May 2021) - Birdsell, Daniel T.; Adams, Benjamin M.; Saar, Martin O.
Abstract: Aquifer thermal energy storage (ATES) is a time-shifting thermal energy storage technology where waste heat is stored in an aquifer for weeks or months until it may be used at the surface. It can reduce carbon emissions and HVAC costs. Low-temperature ( < 25 °C) aquifer thermal energy storage (LT-ATES) is already widely-deployed in central and northern Europe, and there is renewed interest in high-temperature ( > 50 °C) aquifer thermal energy storage (HT-ATES). However, it is unclear if LT-ATES guidelines for well spacing, reservoir depth, and transmissivity will apply to HT-ATES. We develop a thermo-hydro-mechanical-economic (THM) analytical framework to balance three reservoir-engineering and economic constraints for an HT-ATES doublet connected to a district heating network. We find the optimal well spacing and flow rate are defined by the "reservoir constraints" at shallow depth and low permeability and are defined by the "economic constraints" at great depth and high permeability. We find the optimal well spacing is 1.8 times the thermal radius. We find that the levelized cost of heat is minimized at an intermediate depth. The minimum economically-viable transmissivity (MEVT) is the transmissivity below which HT-ATES is sure to be economically unattractive. We find the MEVT is relatively insensitive to depth, reservoir thickness, and faulting regime. Therefore, it can be approximated as 5 ⋅ 1 0 − 13 m 3 . The MEVT is useful for HT-ATES pre-assessment and can facilitate global estimates of HT-ATES potential. Highlights: Novel thermo-hydro-mechanical-economic (THM) analytical approach for HT-ATES. Optimal well spacing, flow rate, and depth. Minimum transmissivity useful for local and global pre-assessment of ATES potential.